The Relationship of Heavy Metals With Lung Cancer: A Systematic Review: Hubungan Logam Berat Dengan Kanker Paru: Sebuah Tinjauan Sistematis - Mohammed, Mostafa Salim (Universitas Muhammadiyah Sidoarjo, 2024)
General Background: Heavy metals such as lead, cadmium, nickel, and copper are known environmental pollutants with established toxic effects on human health. Specific Background: These elements have been identified as significant contributors to various diseases, with emerging evidence suggesting their role in promoting cancer, particularly lung cancer. Knowledge Gap: Although numerous studies have investigated the relationship between heavy metals and lung cancer, a comprehensive understanding of the impact of various metal concentrations on cancer development and progression remains underexplored. Aims: This systematic review aims to consolidate and analyze the existing literature on the effects of heavy metal exposure on lung cancer, focusing on different biological samples such as plasma, urine, nails, and hair. Results: The review identified consistent evidence linking increased levels of heavy metals with higher risks of lung cancer. Studies highlighted the role of metals like cadmium, chromium, and nickel in not only promoting cancer growth but also in impacting the efficacy of cancer treatment. The findings suggest that exposure to these metals, often from environmental and industrial sources, is a critical risk factor for lung cancer. Novelty: This review uniquely synthesizes data from diverse biological samples, providing a holistic view of how heavy metal exposure influences lung cancer. Implications: The study underscores the importance of monitoring and regulating heavy metal exposure to reduce the incidence of lung cancer. It also emphasizes the need for further research to develop targeted strategies for mitigating the risks associated with heavy metal-induced carcinogenesis. Highlights: Heavy metals like cadmium increase lung cancer risk significantly. Diverse samples (plasma, urine) reveal metals' impact on cancer. Regulating metal exposure is key to preventing lung cancer. Keywords: Heavy Metals, Lung Cancer, Cadmium, Carcinogenesis, Toxic Exposure